PENETRASI BANK ASING DAN PENGARUHNYA TERHADAP KOMPETISI PERBANKAN YANG DIUKUR DENGAN PENDEKATAN CONJECTURAL VARIATION DI INDONESIA - Bahtiar Usman (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2013)
This study examines the effect of foreign bank penetration on banking competition in Indonesia. Penetration of foreign banks is measured by using the ratio between total assets, total loans and total deposits of foreign banks to total assets, total loans and total deposits of the banking industry in Indonesia, such as those used by Levy and Micco (2007). Bank concentration is measured by using Concentration Ratio (CR3 and CR5) and the Herfindahl index. Bank competition is measured by using the Conjectural Variation approach as used by Cetorelli Angelini (2003). By using panel regression method with SUR (Seemingly Unrelated Regression) during 1998 to 2009, we found that the increase of foreign bank penetration will increase competition of banking in Indonesia through spillover effects on the domestic banking system. These results support the research of Jeon et al (2011).Keywords: Foreign Bank Penetration, Conjectural Variation and Bank Competition